Karaoke queen - Lim, Dominic, 1974- (Forever, Hachette Book Group, 2024)
"When Rex's ex-boyfriend, Aaron, confides in him about his failing karaoke bar, Rex has a brilliant plan to save it and hopefully rekindle their lost spark. Because straight-laced Rex has a secret weapon, his drag alter-ego Regina Moon Dee, whose master MC'ing abilities might finally turn the bar into a success. The only problem? Rex is too afraid to let Aaron know about his other identity. Will he continue to hide behind Regina to save the bar and his romance with Aaron? Or will he risk everything to tell the truth and find someone who loves him for all he truly is?"--